Some Theoretical Insights on Social Movements and Resistance Practices in the Era of De-Politicization of Representative Politics - de Nardis, Fabio; Antonazzo, Luca (SocietàMutamentoPolitica, 2017)
The global economic crisis of 2008 has fostered a new wave of de-politicization intended as the shifting of national policy making from the public political arena to the field of extra-political supranational and international actors. The public policy making has become tightly linked to criteria that are much more economic than political. This change has provoked a consequent mutation in the nature and behavior of social movements which has result in different kinds of crossbreeding. Traditional social movements with their State-addressed requests have given way to new forms of social conflict that do not directly address to the national government. These new forms of mobilization act primarily in the form of direct social actions aimed at impacting directly on the economy and the environment. The common element of such experiences can be identified in the mix of resilience and resistance that they express.